(untitled) (Research, Society and Development, 2021)
The worsening of the nutritional status during hospitalization negatively affects the patient’s clinical status, because physiological changes may occur as a result of an adaptive process of the body to the lack of nutrients. In this sense, the present article aimed to discuss hospital gastronomy strategies aimed at the acceptance of diets, in order to help prevent hospital malnutrition. This is an integrative literature review. Searches were made in the National Center for Information Technology (PUBMED), Scientific Electronic Library Online (SciELO) databases, and in books on the subject, between 1997 and 2021. The studies showed that hospital malnutrition is a multifactorial condition, with a prevalence between 20% and 50% of inpatients worldwide, which significantly increases morbidity, mortality, length of hospital stay, and hospital readmission rate. Reduced food intake is one of the causes of hospital malnutrition, and may be associated with low diet acceptance. Thus, the application of hospital gastronomy techniques that enable the improvement of sensory characteristics of the preparations are essential tools to increase the acceptance of the preparations offered to patients, favoring the maintenance and/or recovery of the nutritional status, as well as the reduction of food waste. Further studies on this theme should be conducted to evaluate and develop new strategies for hospital gastronomy applied to diet therapy.